Advancing a global collaborative partnership framework for sustainability standards and regulations - Halimatussadiah, Alin; Buchori, Damayanti; Carazo, Felipe; Swinnen, Johan; Adriansyah, Muhammad; Ghiffari, Muhammad Nur; Algamar, Rizal; Anky, Wildan Al Kautsar (T20 India, 2023)
Along with rising trade interdependency between the Global South and the Global North countries, there is growing pressure to implement ‘greener’ supply chains to ensure that traded commodities comply with sustainability norms. Sustainable standards and regulations are broadening their scope to take into account such concerns. Northern stakeholders play a far more extensive role in these processes, while their Southern counterparts are relegated to mere standard-takers as producers. Consequently, it is becoming increasingly challenging for Southern countries to meet sustainability standards, as these drive up their social and economic expenses. To address this, both sides need to make a concerted effort, in accordance with the reforms driving the development of these standards and regulations. Standards need to be globally agreed upon, built through multi-stakeholder forums, and followed up by cushioning financing facilities and mechanisms.